Hubungan Pengetahuan dan Motivasi dengan Kepatuhan Manajemen Diri Perawatan Hemodialisa pada Pasien GGK di RSI PKU Muhammadiyah Pekajangan Pekalongan - Eka Jamilatur Rosyidah; Rita Dwi Hartanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
CKD is a disease of failure of kidney function in maintaining metabolism, fluid and electrolyte balance due to progressive destruction of kidney function. One of the important pillars of this disease is self-management of hemodialysis (HD) care with adherence to self management of it which includes medication adherence, activity management, diet management, fluid restriction, therapy management and psychological response management can lead to an increase in the quality of life of its p[atient. This study aims to determine the relationship between knowledge and motivation with self-management adherence to HD care in CKD patients at RSI PKU Muhammadiyah Pekajangan Pekalongan. The sample is CKD patients undergoing HD as many as 61 respondents. The research use descriptive corellative design. Sampling was carried out using the totalpopulation technique. Univariate and bivariate data analysis in this study use the chi square test. The result of this study indicate that there is a relationship between knowledge and adherence to self-management of HD care with p value 0.000 (p>α) and there is no relationship between motivation and adherence to self-management of HD care with p value 0.732 (p>α). The conclusion self-managementof HD care is one of the care management needed by HD patients. Self-management adherence to HD care is an important factor in the success of HD therapy. The role of nurse and families as well as healtheducation is needed to support HD care self-management compliance and addition to patient knowledge and motivation.